An optical fiber sensing method for partial discharge in the HVDC cable system. (June 2021) - Liu, Zhiheng; Wang, Yongqing; Chen, Xiao; Meng, Xiaokai; Liu, Xiuling; Yao, Jianquan
Highlight: The influence of the optimal detection position of partial discharge and the number of optical fiber sensing probes on the sensitivity of the optical fiber sensing system is studied. The ultrasonic spectrum range of the partial discharge detection system is verified through experiments, and the characteristic frequency of partial discharge is obtained. It is verified based on the ultrasonic location detection of partial discharge in 15 km HVDC cable system, and the positioning deviations is less than 80 m. Abstract: To improve the safety and efficiency performance of partial discharge detection in a high-voltage direct current (HVDC) cable system, an optical fiber ultrasonic detection system for partial discharge is carried out in the long-distance HVDC operating environment. The correlation model between partial discharge ultrasonic wave and discharge quantity is established by analyzing the partial discharge mechanism and ultrasonic characteristics of DC cable. The partial discharge repetition rate and discharge magnitude of several common insulation defects are obtained experimentally, and the ultrasonic characteristic Sagnac fiber detection system is accomplished based on the data above. Then, the standard ultrasonic time-domain signal detection and fiber optic sensing probe directional experiment are fulfilled, and the ultrasonic wave is measured based on fiber-optic probe and can perform multi-point detection. The influence of different length fiber sensing probes on the sensitivity of partial discharge signals is investigated based on the frequency distribution characteristics of partial discharge. The effectiveness of the optical fiber sensing system is verified based on the zero-frequency point localization method with ultrasonic location detection of partial discharge in a 15 km HVDC cable system. The measurement results obtained show the deviations of determining the location of the partial discharge point is less than ±80 m. The reliability of the proposed PD optical fiber detection system for intrinsic safety and detection efficiency of partial discharge position in the HVDC cable system is verified.